Universities' Role in Knowledge-Based Economy and Society. Implications for Romanian Economics Higher Education - Marta-Christina Suciu; Irina-Virginia Drăgulănescu; Alexandru Ghiţiu-Brătescu; Luciana Picioruş; Cosmin Imbrişcă (Amfiteatru Economic Journal, 2011)
The main objective of the article is to analyse the extent to which Romanian universities and, particularly, those in economics higher education field can face the demands of knowledge-based economy and society. The specific objectives of the work mainly consisted of: (a) reviewing the literature outlining the theoretical, methodological and conceptual boundaries; (b) identifying methods for assessing universities' intellectual capital and examples of good practice; and (c) presenting our research results. The research methodology was based on a structured questionnaire applied in the Academy of Economic Studies, Bucharest, Faculty of Business Administration in foreign languages. Examples of good practice in European universities and international reports of prestigious international organizations were considered as well. The research highlighted the key role of universities as main investors in lifelong learning education, by including the opinions of the direct beneficiars-students, within the context of the Romanian society and knowledge-based economy.
Keywords: A10; D83; E22; I20; J24; 330; Knowledge-based economy; knowledge-based society; investment in lifelong learning education; intellectual capital; sustainable competitive advantage